Pemanfaatan Media Sosial Sebagai Strategi Promosi Bagi Pengembangan Pemasaran Yang Efektif Dalam Menarik Pelanggan Better Bite - Dimas Bagus Satriyo; Syed Fauzan Abubakar; A. Adi Sakhoul Irtifa (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
Social media users in Indonesia are very high, so business actors use social media as a place for promotion and selling. Business people use social media to introduce their products. Social media has useful features for businesses so that they can facilitate promotional activities and sell their products. The author conducted this research, aiming to find out the increase in sales experienced by businesses when using social media in carrying out their marketing strategy, namely promoting their products by utilizing features on social media. This method uses descriptive qualitative research. This research collects data through direct interviews with business actors. The results of this study, namely utilizing social media features, and conducting regular promotions on social media can be one of the marketing strategies. They also take advantage of their relationships, namely using word-of-mouth marketing strategies and consumer reviews so that the products they offer can be reached more widely